Mapping K factor variations and its causes in a modern, spark-ignition engine. (15th April 2021) - Zhou, Zhenbiao; Kar, Tanmay; Yang, Yi; Brear, Michael; Xu, Jingran; Lacey, Joshua; Leone, Thomas; Anderson, James; Shelby, Michael; Curtis, Eric
Highlights: New method developed to determine the K factor in the Octane Index model. K maps obtained for a 2L, 4-cylinder, gasoline turbocharged direct-injection engine. K mostly negative (positive) with normal (high) operation temperatures. K correlated with the unburned gas temperature at the later stages of combustion. Abstract: The Research Octane Number (RON) and the Motor Octane Number (MON) are primary fuel properties that characterize gasoline's knock resistance in spark ignition engines. The utility of these two metrics, however, has been questioned with advancements in engine technologies that significantly change the thermochemical environment inside the cylinder. The Octane Index, OI = (1-K)·RON + K·MON, has therefore been proposed to characterize the knock resistance in modern engines where K weights the relative contribution of the RON and MON and is primarily determined by engine design and operating conditions. Quantifying the K factor is central to understanding a fuel's anti-knock performance in a modern spark-ignition (SI) engine. This work therefore determines the map of K over engine operating conditions for a 2-litre, 4-cylinder turbocharged, gasoline direct-injection engine. To achieve this, a novel blending system for primary reference fuels (PRFs) was developed to determine K by matching the knock resistance of a 91.6-RON certification gasoline with a PRF at each operating condition. The K values are determined over the engine map with normal and high intake air and coolant temperatures. At normal operating temperature, K is negative at most knock-limited conditions, consistent with previous findings, whereas at high operating temperatures, K is mostly positive and, indeed, exceeds 1 near 8 bar BMEP and 3000 RPM, demonstrating the relevance of the MON at some conditions of practical significance. Further analysis is conducted via engine simulations to examine the relationship between K and end gas conditions, and a strong correlation is observed between K and the unburned gas temperature at the later stages of combustion. This correlation is argued to have a sound physical basis in the engine's thermochemistry, supporting the utility of this K factor method.